A dry powder formulation from silk fibroin microspheres as a topical auto-gelling device. (18th May 2016) - Faragò, Silvio; Lucconi, Giulia; Perteghella, Sara; Vigani, Barbara; Tripodo, Giuseppe; Sorrenti, Milena; Catenacci, Laura; Boschi, Alessandra; Faustini, Massimo; Vigo, Daniele; Chlapanidas, Theodora; Marazzi, Mario; et al.
Abstract: With the aim of establishing the formulation of a new hydrophilic auto-gelling medical device for biomedical applications, fibroin-based microspheres were prepared. The proposed microspheres were produced by a cost-effective and industrially scalable technique, such as the spray-drying. Spray-dried silk fibroin microspheres were obtained and the effects of different hydrophilic polymer on the process yield, microsphere morphology and conformation transition of fibroin were evaluated. The final auto-gelling formulations were obtained by adding calcium gluconate (as a calcium source for alginate crosslinking) to the prepared microspheres and tested by an in vitro gelling test. This study showed that the combination of fibroin with sodium alginate and poloxamer produced the most promising auto-gelling formulation for specific biomedical applications, such as the treatment of pressure ulcers.